Security of supply as a political bargaining issue: Why Germany opted against capacity markets. (April 2022) - Gawel, Erik; Lehmann, Paul; Purkus, Alexandra; Söderholm, Patrik; Strunz, Sebastian
Abstract: The large-scale deployment of intermittent renewable energy sources for electricity generation has raised concerns regarding the future security of supply. Previous research has studied efficient reforms of electricity markets to address these concerns. In contrast, our paper aims to explain actual policy choices made to provide security of supply. For this purpose, we develop a Public Choice framework, which looks at three interacting decision variables: the timing of regulatory intervention, the decision-making process and the market design. We apply this framework to study the policy debates and decisions related to Germany's 2016 electricity market reform. The analysis builds on the rich empirical material made available through a consultation process preceding the German parliamentary decision. The electricity market reform eventually combined measures to strengthen the energy-only market and the implementation of only limited new capacity payments through a strategic reserve. This was despite the fact that conventional electricity producers strongly lobbied for a fully-fledged capacity market by which they would have benefited from new broad-band capacity payments. Our analysis suggests that the eventual market design decision was strongly affected by the timing of regulatory intervention (existing oversupply of generation capacity) and the decision-making process (an open consultation process revealing broad opposition against capacity markets).